Capital structure and financial performance of Sri Lankan listed companies: A panel data analysis - Tharsika, K.; Pratheepkanth, P. (University of Vavuniya, 2023)
This study delves into the capital structure debate, examining its impact on financial performance among 50 non-financial firms listed on the Colombo Stock Exchange from 2013 to 2022. It specifically analyses Short-Term Debt to Total Assets Ratio (STDTA), Long-Term Debt to Total Assets Ratio (LTDTA), and Debt-To-Equity Ratio (DTE) as indicators, with Return on Assets (ROA) as the performance metric. Results show a positive link between STDTA and LTDTA with financial performance, while DTE shows no significant correlation. This suggests firms should consider a balanced mix of short- and long-term debt to enhance profitability. Future research could explore qualitative methods for deeper insights into capital structure dynamics and firm value.
Keywords: Capital structure; Financial performance; Modigliani miller theory